Biomechanical properties of anuran long bones: correlations with locomotor modes and habitat use - Vera, Miriam Corina (J Anat, 2020)
Long bones are subjected to mechanical loads during locomotion that will influence their biomechanical properties through a feedback mechanism (the bone mechanostat). This mechanism adapts the spatial distribution of the mineralized tissue to resist compression, bending and torsion. Among vertebrates, anurans represent an excellent group to study long bone properties because they vary widely in locomotor modes and habitat use, which enforce different skeletal loadings. In this study, we hypothesized that (a) the cortical bone mass, density and design of anuran femur and tibiofibula would reflect the mechanical influences of the different locomotor modes and habitat use, and (b) the relationships between the architectural efficiency of cortical design (cross‐sectional moments of inertia) and the intrinsic stiffness of cortical tissue [cortical mineral density; the 'distribution/quality' (d/q) relationship] would describe some inter‐specific differences in the efficiency of the bone mechanostat to improve bone design under different mechanical loads. To test this hypothesis, we determined tomographic (peripheral quantitative computed tomography) indicators of bone mass, mineralization, and design along the femur and tibiofibula of four anuran species with different modes of locomotion and use of habitat. We found inter‐specific differences in all measures between the distal and proximal ends and mid‐diaphysis of the bones. In general, terrestrial‐hopper species had the highest values. Arboreal‐walker species had the lowest values for all variables except for cortical bone mineral density, which was lowest in aquatic‐swimmer species. The d/q relationships showed similar responses of bone modeling as a function of cortical stiffness for aquatic and arboreal species, whereas terrestrial‐hoppers had higher values for moments of inertia regardless of the tissue compliance to be deformed. These results provide new evidence regarding the significant role of movement and habitat use in addition to the biomechanical properties of long bones within a morpho‐functional and comparative context in anuran species.